Spontaneous Retroperitoneal Haematoma due to Polyarteritis Nodosa: Report of a Case and Literature Review. (18th January 2016) - Simsek, Emrah; Yilmaz, Hasan; Teke, Kerem; Uslubas, Ali Kemal; Yuksekkaya, Mustafa
Abstract : Retroperitoneal haematoma is a rare clinical entity with variable etiology. It can happen spontaneously, without any obvious precipitating factors, the so-called spontaneous retroperitoneal haematoma. There is no general consensus as to the best management plan for patients with retroperitoneal haematoma. Polyarteritis nodosa (PAN) is a rare cause of retroperitoneal haematoma. Here we report relationship between PAN and retroperitoneal haematoma and treatment approaches. However, an accepted and clearly defined treatment has not been established due to its rarity.